Assessment of variables associated with prolonged admission duration in children with Mycoplasma pneumoniae pneumonia. (7th October 2022) - Sung, Myongsoon; Roh, Eui Jeong; Lee, Eun Sil; Lee, Ji Young; Kim, Hyo‐Bin; Ahn, Youngmin; Eun, Byung Wook; Kim, Ja Kyoung; Kim, Hyoung Young; Jung, Sung‐Su; Kim, Minji; Kang, Eun Kyeong; et al.
Abstract: Introduction: Macrolide‐resistant Mycoplasma pneumoniae (MRMP) has become prevalent in children. This study investigated the clinical and laboratory variables of MRMP and macrolide‐sensitive M. pneumoniae (MSMP) and identified factors associated with prolonged hospital admission in children. Methods: A prospective multicenter study was conducted in 1063 children <18 years old in July 2018–June 2020. The 454 had a positive M. pneumoniae polymerase chain reaction assay. Results: Most subjects had MRMP (78.4%), and all mutated strains had the A2063G transition. We defined MRMP* ( n = 285) as MRMP pneumonia requiring admission and MSMP* ( n = 72) as MSMP pneumonia requiring admission. Patients with MRMP pneumonia were older, more likely to have segmental/lobar pneumonia, and had more febrile days than those with MSMP pneumonia. C‐reactive protein (CRP), lactate dehydrogenase (LDH), and percentage neutrophils were more strongly associated with MRMP* than MSMP* groups. Percentage neutrophils, CRP, and alanine aminotransferase significantly changed between admission and follow‐up measurements in patients with MRMP* ( P < 0.05). The duration of admission positively correlated with the number of febrile days after initiation of antibiotic medication and laboratory variables (white blood cell count, CRP, and aspartate aminotransferase [AST]) ( P < 0.05). Random forest analysis indicated that the number of febrile days after initiation of antibiotic medication, AST, and percentage neutrophils at admission was over five. Conclusions: This study indicated that children with M. pneumoniae pneumonia with a higher number of febrile days after initiation of antibiotic medication, AST, and percentage neutrophils at admission were more likely to have prolonged admission duration. Abstract : Macrolide‐resistant Mycoplasma pneumoniae (MRMP) has become prevalent in children. Children with M. pneumoniae pneumonia with a higher number of febrile days after initiation of antibiotic medication, AST, and percentage neutrophils at admission were more likely to have prolonged admission duration.